Gear Up, Mishaps down The Evolution of Naval Aviation Safety, 1950-2000. (Naval Institute Press, 2017)
"Less than five years after naval aviation had been in the forefront of the forces that defeated Imperial Japan, it found itself in serious trouble. One of the first steps to re-order priorities and save naval aviation was to solve the problem of increasing numbers of accidents. Over the next fifty years that problem was indeed solved to the extent that today, despite hot wars, cold wars, contingencies and peacetime operations in support of friends and allies the Navy/Marine accident rate is at least as good as that of the Air Force and approached that of commercial aviation. The keys to how this was achieved lies with dedicated and professional leadership, a focus on lessons learned from mishaps and near-mishaps, a willingness to learn and adopt new leadership, training, management, maintenance and supply styles and procedures. All this and more is described in this book."--Provided by publisher.